2021
DOI: 10.1149/2162-8777/abefaf
|View full text |Cite
|
Sign up to set email alerts
|

Review—A Review of 2D Perovskites and Carbon-Based Nanomaterials for Applications in Solar Cells and Photodetectors

Abstract: Photonic devices such as solar cells and photodetectors that produce electricity play a vital role in our daily life for applications such as fibre optic communication systems, process control, and also in defence related applications. Today, two-dimensional perovskites that belong to the class of emerging materials show promising energy applications. 2D perovskites have been investigated for their exceptional properties such as high optical absorption coefficients, structural diversity and tuneable bandgaps w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 111 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…However, the large dark current due to the gapless nature and high conductivity of graphene has a strong adverse impact on the PDs detectivity and hinders these devices in some applications 239,253,254 . On the other hand, devices based on perovskite with TMDs hybrid structures showed a balanced performance 98,163,219,221,255 . In this section we discuss the state-of-the-art perovskite/TMD PDs starting with MAPbI 3 /TMD HSs as the mostly studied perovskite/TMD PDs then CsPbBr 3 /TMD HSs followed by other perovskite/TMD HSs.…”
Section: Photodetectors (Pds)mentioning
confidence: 99%
“…However, the large dark current due to the gapless nature and high conductivity of graphene has a strong adverse impact on the PDs detectivity and hinders these devices in some applications 239,253,254 . On the other hand, devices based on perovskite with TMDs hybrid structures showed a balanced performance 98,163,219,221,255 . In this section we discuss the state-of-the-art perovskite/TMD PDs starting with MAPbI 3 /TMD HSs as the mostly studied perovskite/TMD PDs then CsPbBr 3 /TMD HSs followed by other perovskite/TMD HSs.…”
Section: Photodetectors (Pds)mentioning
confidence: 99%
“…Since Geim's successful preparation of single-layer graphene from graphite in 2004 [1], this material has attracted widespread attention due to its exceptional physical and electrochemical properties, including being a two-dimensional (2D) carbon material with excellent gas adsorption, high strength, ultra-low weight, low resistivity, and a room temperature Hall effect [2][3][4][5][6]. Despite its wide applications in sensors, biomaterials, energy, and other fields [7][8][9], graphene still lacks semiconductor properties due to its zero band gap. Furthermore, its high production cost and limited scalability restrict its application exclusively to high-end industries [10].…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite materials, owing to their high carrier mobility, effective charge collection, efficient light absorption, and low-cost preparation by the solution method, are widely used as active layer materials in solar cells and photodetectors. , It was reported that the absorption range of perovskite materials can be effectively adjusted by changing the composition ratio of Cl – , Br – , and I – anions, which makes it possible to prepare a series of visible-blind spectrum tunable NIR photodetectors based on perovskite or perovskite/organic hybrid active layers. Lan et al reported the structure of CH 3 NH 3 PbI 3 (1700 nm)/PTB7-Th:PC 71 BM (200 nm) to accomplish an NIR narrowband perovskite-organic hybrid PDs with the CCN strategy.…”
Section: Introductionmentioning
confidence: 99%